Informativeness of ground penetrating radar method for investigations of the glaciers on Galindez, Winter and Skua islands (the Argentine Islands, results for the period April tо November 2017) - A. P. Chernov (Ukrainian Antarctic Journal, 2017)
In this paper results of ground penetrating radar (GPR) surveying of island’s glaciers are shown. The main objectives were testing of VIY-3 300 GPR in weather conditions of Antarctica and check which information about glaciers can be obtained with this equipment. Methods: results of GPR surveying on Galindez Іsland were compared with results of video-impulse radiolocation method (1998 year), vertical electric-resonance sounding (2004 year) and meteorological data (2014-2017). Common offset modification of the GPR method was applied; central frequency of ground coupled antenna: 300 MHz. Results: GPR profiles were recorded along 2 glaciers on Winter island, 2 glaciers on Skua island and along 1 glacier on Galindez island. Several anomalies were indicated, which interpreted as layering of the ice, glacier’s bed, fissures, voids, areas of higher moisture content and potential glacier conduits. Further GPR monitoring of the glaciers’ interior should be done to obtain clear information about mentioned heterogeneities and about their future development. Conclusions: VIY-3 300 GPR works properly in conditions of Antarctica and is suitable for identification of heterogeneities in glaciers up to 27.5 meters. Mentioned equipment can be easily transported, recording of the profiles on mentioned glaciers could be done by one person. Speed of work is 300 meters in 20 minutes for new area (first time surveying on glacier) and 600 meters in 30 minutes for monitoring site (while monitoring on Galindez island).